Antioxidant Vitamins in the Prevention of Atrial Fibrillation: What Is the Evidence? - Sonia Rasoli; Nicholaos Kakouros; Leanne Harling; Philemon Gukop; Manish Soni; Thanos Athanasiou; Antonios Kourliouros (Cardiology Research and Practice)
Atrial fibrillation (AF) is the most common sustained arrhythmia that is associated with significant morbidity and mortality. Current available therapies remain inadequate in symptom control and secondary prevention and are often associated with significant side effects. The mechanisms underlying the pathogenesis of AF are poorly understood, although electrophysiological remodeling has been described as an important initiating step. Recently, increasing evidence implicates oxidative stress and inflammation in the pathogenesis of AF. We searched the literature for evidence to support the use of antioxidant vitamins C and E in the prevention of AF. These vitamins, through their reactive-oxygen-species- (ROS-) scavenging effect, have shown a role in AF prevention in both animal and small clinical studies. The available evidence, however, is currently insufficient to support recommendations for their use in the wider patient population. Larger-scale clinical studies are required to confirm these preliminary results. Research is also required to further the understanding of the processes involved in the pathogenesis of AF and the role of antioxidant therapies to prevent the arrhythmia.